ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM FILM BUMI TADULAKO KARYA PUSDATIN - Nuli, Wafak Fatkul; Pratiwi, Ika Ari; Ardianti, Sekar Dwi (Universitas Muria Kudus, 2022)
This study aims to describe the analysis of character education values in the film Bumi Tadulako by Pustadin. This study uses qualitative research with a critical discourse analysis method approach. Data collection is done by observation, interviews, documentation. The research was conducted at SDN Wegil Sukolilo Pati. The object of research is the values of character education in films in Civics learning in elementary schools, where the fourth grade teacher is the facilitator and the research subject is the fourth grade student informant consisting of 6 students, 3 boys and 3 girls. The data analysis used by the discourse analysis technique focuses on two elements, namely, first, at the word level and second, how the events and actors involved in an event are about to be discussed. The results showed that there were values of character education in the film